2016
DOI: 10.1080/19443994.2015.1019362
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption behavior of Sr2+ using straw-derived biochar: equilibrium and isotherm study

Abstract: A B S T R A C TRice straw-derived biochars carbonize at different temperature (550, 650, 750˚C) used for Sr 2+ removal. Experimental parameters affecting the sorption process like pH, contact time, sorbent concentration, and temperature were investigated. Sorption profile showed an initial rapid uptake which decreased and became almost constant after one hour. Optimum Sr 2+ sorption was achieved at pH 6. Sorption kinetics good correlated with both pseudo-secondorder and Elovich kinetic equations. Isotherm mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The observed increase in MEB removal could be due to the nanosize and amorphous nature of ARHB as large surface area are exposed per unit mass of the ARHB. This observation is in agreement with the studies [15,24,27,41] on the removal of azo dyes from various agricultural waste biochar.…”
Section: Effect Of Initial Meb Concentration and Time Of Contactsupporting
confidence: 93%
See 1 more Smart Citation
“…The observed increase in MEB removal could be due to the nanosize and amorphous nature of ARHB as large surface area are exposed per unit mass of the ARHB. This observation is in agreement with the studies [15,24,27,41] on the removal of azo dyes from various agricultural waste biochar.…”
Section: Effect Of Initial Meb Concentration and Time Of Contactsupporting
confidence: 93%
“…Recently, the development and use of various adsorption materials, techniques and technologies for the removal of contaminants from aqueous media have increased [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Many researchers [15][16][17][18][19][20][21][22][23][24][25][26][27] have used many agricultural based waste materials such as Retama Raetam plant, saw dust, wheat bran, Jatropha Curcas and Terminalia Catappa and unmodified saw dust as an alternative cheaper and affordable substitute for application as sorbent for adsorption of contaminants from aqueous media. Rice husks are waste materials from rice processing and are usually discarded indiscriminately or burnt sometimes leading to eutrophication and green house aerosols, carbon (IV) oxide, carbon(II)oxide, methane, nitrogen oxides and volatile organics which present serious health and climatic changes [27][28][29][30][31][32][33][34][35][36] Varieties of synthetic anionic and cationic dyes are routinely used by chemical industries such as leather, textile, printing, food, pulp and paper [27] .…”
Section: Introductionmentioning
confidence: 99%
“…This model states; if the plot of q t against √t is straight and passing through origin then the sorption is considered to occur via intra-particle diffusion and the rate controlling step only depends upon it, while if it is not passing from the origin it gives the indication that at the same time some other kinetic phenomenon may be responsible for rate-controlling step. 26 In current study, plot of qt against √t is linear but it does not pass through origin shown in Fig. 9 Which is indicating that sorption rate is controlled by some other kinetic phenomenon and all of which may be operating at the same time.…”
Section: Morris-weber Model (Intra-particle Diffusion Model)mentioning
confidence: 56%
“…The plot is not linear over the whole time range, which indicates that more than one step is involved in the sorption of MO. As the plot does not pass through the origin, intraparticle diffusion is not the only rate‐limiting step . It is clear that the plot shows two intersecting sharp lines, where the first line may be attributed to the fast surface adsorption of MO molecules on the sorbent, while the second line represents the slow diffusion stage where intraparticle diffusion is rate‐limiting.…”
Section: Resultsmentioning
confidence: 96%